METHODS OF FORMING STUDENTS’ CREATIVE-CRITICAL THINKING SKILLS - Shukhratjon Ismoiljonov Boymirza o’g’li (Research Focus International Scientific Journal, 2023)
The modern world requires individuals with a wide range of skills, including cognition, the application of many modes of thought, research, problem-solving ability, critical thinking abilities, and creativity. Learning styles are another important aspect, along with critical thinking, that play a crucial part in the process of issue solving. This study aimed to determine the importance and the ways of teaching and learning styles and critical thinking of students in their academic performance.